Canted magnetic ground state of quarter-doped manganites R0.75Ca0.25MnO3 (R = Y, Tb, Dy, Ho, and Er). (21st December 2016) - Sinclair, R; Cao, H B; Garlea, V O; Lee, M; Choi, E S; Dun, Z L; Dong, S; Dagotto, E; Zhou, H D
Abstract: Polycrystalline samples of the quarter-doped manganites R 0.75 Ca0.25 MnO3 ( R = Y, Tb, Dy, Ho, and Er) were studied by x-ray diffraction and AC/DC susceptibility measurements. All five samples are orthorhombic and exhibit similar magnetic properties: enhanced ferromagnetism below T 1 (̃80 K) and a spin glass (SG) state below T SG (̃30 K). With increasing R 3+ ionic size, both T 1 and T SG generally increase. The single crystal neutron diffraction results on Tb0.75 Ca0.25 MnO3 revealed that the SG state is mainly composed of a short-range ordered version of a novel canted (i.e. noncollinear) antiferromagnetic spin state. Furthermore, calculations based on the double exchange model for quarter-doped manganites reveal that this new magnetic phase provides a transition state between the ferromagnetic state and the theoretically predicted spin-orthogonal stripe phase.